2011
DOI: 10.1089/hum.2011.002
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Signaling Contributes to the Innate Immune Response Against Helper-Dependent Adenovirus Vectors Independently of MyD88 In Vivo

Abstract: We previously demonstrated that Toll-like receptor/myeloid differentiation primary response gene 88 (MyD88) signaling is required for maximal innate and acquired [T helper cell type 1 (Th1)] immune responses following systemic administration of helper-dependent adenoviral vectors (HDAds). However, MyD88-deficient mice injected with HDAdLacZ exhibited only partial reduction of innate immune cytokine expression compared with wild-type mice, suggesting MyD88-independent pathways also respond to HDAds. We now show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…It was also suggested that the cytosolic sensors of the nucleotide-binding and oligomerization domain (NOD) family receptor, NOD2, and a NOD-like (NLR) family receptor, NLRP3, contribute to the detection of HAdv in the cytosol [72,73]. Suzuki et al [72] have shown that the intravenous administration of HAdv-C5-based vector triggered reduced levels of activation of the inflammatory cytokines IL-6, TNF-a, and IL-12p40 and chemokines CCL2 and CCL5 in the livers of Nod2 À/À mice, compared to control wild-type mice, when analyzed 6 h after the intravenous virus administration. Muruve et al [73] have demonstrated that 6 h after intravenous administration of HAdv5based vector, the amounts of inflammatory cytokines IL-1b and IL-6 and chemokines CCL2, CCL4, and CXCL10 were significantly lower in the spleens of Nlr-p3 À/À mice compared to WT mice.…”
Section: Innate Immune Signaling Pathways Activated Upon Hadv Entry Imentioning
confidence: 99%
“…It was also suggested that the cytosolic sensors of the nucleotide-binding and oligomerization domain (NOD) family receptor, NOD2, and a NOD-like (NLR) family receptor, NLRP3, contribute to the detection of HAdv in the cytosol [72,73]. Suzuki et al [72] have shown that the intravenous administration of HAdv-C5-based vector triggered reduced levels of activation of the inflammatory cytokines IL-6, TNF-a, and IL-12p40 and chemokines CCL2 and CCL5 in the livers of Nod2 À/À mice, compared to control wild-type mice, when analyzed 6 h after the intravenous virus administration. Muruve et al [73] have demonstrated that 6 h after intravenous administration of HAdv5based vector, the amounts of inflammatory cytokines IL-1b and IL-6 and chemokines CCL2, CCL4, and CXCL10 were significantly lower in the spleens of Nlr-p3 À/À mice compared to WT mice.…”
Section: Innate Immune Signaling Pathways Activated Upon Hadv Entry Imentioning
confidence: 99%
“…Splenocytes were collected from each group of mice (Suzuki et al, 2011). One million splenocytes were washed with stain buffer and used for immediate ex vivo analysis by flow cytometry.…”
Section: Splenocyte Culture Assaymentioning
confidence: 99%
“…We and another group have reported that NOD2 and NLRP3 recognize Ad vector DNA, likely via the NBD, independent of vector sequences and induce pro-inflammatory cytokines in vivo [39,40]. Our data showed that HDAd injected NOD2 deficient (NOD2 −/− ) mice and infected NOD2 −/− mouse derived embryonic fibroblasts (MEFs) show a significant reduction of inflammatory cytokine expression at both the RNA and protein levels compared to WT mice.…”
Section: The Innate Inflammatory Response To Ad-based Vectors May mentioning
confidence: 56%